The Effect of Pyrolysis Conditions on the Preparation of Fe2O3 Particles Using Simulated Pickling Liquor in a Venturi Reactor - Lv, Chao; Sun, Ming-He; Yin, Hong-Xin (Frontiers in Materials, 2021)
Large amounts of pickling liquor are produced during the pickling of iron and steel. The Venturi reactor is used during the pyrolysis of pickling liquor to prepare high-purity Fe2O3 particles. Changing the pyrolysis conditions will affect the purity and concentration of Fe2O3 particles. In this paper, physical experiments and numerical simulations were carried out to study the effect of pyrolysis conditions on the Fe2O3 particles, including the pyrolysis temperature, the FeCl2/FeCl3 ratio in the pickling liquor, and the citric acid ratio. The results showed that a product with a higher purity, better crystallinity, and greater concentration was obtained at 923 K. Further increasing the temperature did not change the concentration of Fe2O3 particles. When the ratio of FeCl2/FeCl3 in the pickling liquor was 1:1.5, the maximum concentration of Fe2O3 particles at the outlet was obtained. When the added proportion of citric acid was 1:1, the particle size distribution was more uniform, and when the added proportion was 1:2.5, the maximum concentration of Fe2O3 particles at the outlet was achieved.